The design of Dominantly Inherited Alzheimer Disease Trial of the anti‐tau antibody, E‐2814, on the DIAN‐TU Tau Next Generation Platform. (31st December 2021) - Schneider, Lon S.; Bateman, Randall J.; Clifford, David B.; McDade, Eric; Wang, Guoqiao; Llibre‐Guerra, Jorge J.; Li, Yan; Mills, Susan; Santacruz, Anna; Sachdev, Pallavi; Li, David JianJun; O'Sullivan, Stacie; et al.
Abstract: Background: Tau pathology is closely associated with the onset and progression of Alzheimer's disease. Recent advances in drugs that target tau suggest the potential to prevent or attenuate the pathophysiology and pathology of tau. Novel CSF and blood tau species including specific phospho‐tau (p‐tau) and truncated species containing the microtubule binding region of tau (MTBR‐tau) which aggregates in tau tangles, increases 10 years or more before tau tangles are detected by tau‐PET. Two stages of AD are identified and studied using soluble p‐tau and MTBR‐tau forms in the asymptomatic stage and Tau PET in the post‐tangle symptomatic stage. E2814, an anti‐tau monoclonal antibody targets MTBR‐tau and decreases tau pathology in animal models. Method: We designed an anti‐tau trial to target soluble tau species in two cohorts including pre‐tangle asymptomatic and post‐tangle symptomatic participants in dominantly inherited AD (DIAD). We analyzed longitudinal clinical, cognitive, tau PET and CSF measures of tau species including, multiple p‐tau species (e.g., p‐tau217, 231, 181, 205), total tau, MTBR‐tau (e.g., MTBR‐tau243, MTBR‐tau299, and MTBR‐tau354), and NfL in DIAD cohorts from DIAN and DIAN‐TU. Novel trial design and statistical approaches have been developed to address primary and secondary outcomes, magnitude of effect by stage of disease (pre‐tangle vs. post‐tangle), and potential for prevention. Result: We designed a trial of two cohorts, each powered, with different biomarker outcomes: in the pre‐tangle, tau‐PET negative cohort, CSF ptau217/tau217 is the endpoint; for the post‐tangle tau‐PET positive cohort, tau‐PET is the endpoint. Further, each cohort will measure target engagement by CSF MTBR‐tau and downstream effects on soluble total tau, p‐tau and MTBR tau with common measures of neurodegeneration by CSF and blood NfL, atrophy by MRI, hypometabolism by FDG‐PET, effects on amyloid by abeta42/40 and amyloid‐PET, and cognitive and clinical measures. This design is facilitated by the predictable pattern of biomarker changes observed in DIAD allowing appropriate powering of the study even in this rare condition. Conclusion: The Tau Next Generation Platform will address disease progression, before and after tangle formation begins, assessing when an anti‐MTBR tau monoclonal antibody will have the largest effects. It is the first anti‐tau trial for DIAD.